2003
DOI: 10.1016/j.cub.2003.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization and Transcriptional Repression Are Confined to Separable Domains in the Circadian Protein CRYPTOCHROME

Abstract: Circadian rhythms are driven by molecular clocks composed of interlocking transcription/translation feedback loops. CRYPTOCHROME (CRY) proteins are critical components of these clocks and repress the activity of the transcription factor heterodimer CLOCK/BMAL1. Unlike the homologous DNA repair enzyme 6-4 PHOTOLYASE, CRYs have extended carboxyl-terminal tails and cannot repair DNA damage (reviewed in ). Unlike mammals, Xenopus laevis contains both CRYs (xCRYs) and 6-4 PHOTOLYASE (xPHOTOLYASE), providing an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 20 publications
5
42
0
3
Order By: Relevance
“…6E). Introduction of CLOCK on its own slightly increased Per1 promoter-dependent gene expression, whereas the combined expression of wild-type CLOCK and BMAL1 caused a marked increase that was abolished by CRY1, as described previously (22,52). In sharp contrast, when either component of the CLOCK/BMAL1 heterodimer was replaced with a mutant lacking an essential domain for transactivation, the dimeric transcription factor no longer elicited robust induction of reporter gene expression.…”
Section: Vol 26 2006 Bmal1 Shuttling Controls Circadian Gene Expressupporting
confidence: 71%
“…6E). Introduction of CLOCK on its own slightly increased Per1 promoter-dependent gene expression, whereas the combined expression of wild-type CLOCK and BMAL1 caused a marked increase that was abolished by CRY1, as described previously (22,52). In sharp contrast, when either component of the CLOCK/BMAL1 heterodimer was replaced with a mutant lacking an essential domain for transactivation, the dimeric transcription factor no longer elicited robust induction of reporter gene expression.…”
Section: Vol 26 2006 Bmal1 Shuttling Controls Circadian Gene Expressupporting
confidence: 71%
“…As a result of our random mutagenesis screen, we generated many novel mutant Cry alleles. The residue changes corresponding with defects in transcriptional repression were confined to the PHR, and no changes were observed in the Cterminal tail, which has been shown to be important for nuclear localization in mammals (4,20) and Xenopus (31). This is in line with data from Chaves et al (4), who reported that interaction of mCRY1 with BMAL1 via the coiled-coil domain in its PHR could facilitate CRY's nuclear localization, even in the event that its NLSs are mutated.…”
Section: Random Mutagenesis and Cell-based Functional Screen Ofmentioning
confidence: 98%
“…The main body of the protein, called the photolyase homology region (PHR), has been shown to be sufficient to repress CLOCK-BMAL1 in Xenopus laevis. (31) and is well conserved between CRY1 and CRY2. While it has been shown that CRY binding with CLOCK-BMAL1 is required for repression of their transcriptional activity (21), the mechanism by which the repression occurs is not known.…”
mentioning
confidence: 99%
“…5, right lower alignment). The C-tail of amCRY does not contain a second putative NLS found on the C-tails of mCRY2 and xCRY2b (Zhu et al 2003;Sakakida et al 2005;Chaves et al 2006). These analyses show that amCRY does not contain sequences thought to be necessary for dCRY photoreceptor function.…”
Section: Genome Research 1355mentioning
confidence: 99%